NEEDS ANALYSIS FOR ENGLISH DISCOURSE TEXTBOOKS EVALUATION FOR INDONESIAN STUDENTS: GRADUATE STUDENTS’ PERCEPTION - Badi’atul Azmina; Dyah Fitri Mulati; Khotimah Mahmudah; admin, admin (Aisyah Journal of English Language Teaching (AIJELT), 2024)
This study aims to uncover the perceptions of graduate students on the content, examples, exercises/tasks, and presentation/format of the textbook "Analisa Wacana dan Pengajarannya" for the subject of Discourse Analysis and Language Teaching (DA and LT). This descriptive qualitative research involved students’ perceptions of the selection of discourse textbooks in relation to their needs as the object of the research. Meanwhile, the subjects of the research were graduate students of the English Education Department in one of the state universities in Surakarta, Indonesia. The data collection methods utilized were the administration of questionnaires and document analysis. The findings revealed that nearly all students expressed a favorable response about the analysis of the textbook, including its content, examples, exercises/tasks, and presentation/format. Nevertheless, several comments provided valuable input to the instructor of the DA and LT Subject, prompting revisions to certain sections of the book.